2022
DOI: 10.3390/life12081177
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soft Contact Lens Wear on The Tear Film and Meibomian Gland Drop-Out and Visibility

Abstract: As contact lens (CL) wear affects the ocular surface, this cross-sectional study aims to assess the effects of soft CL wear and its duration on the tear film and meibomian gland (MG) drop-out and visibility. Thirty non-CL wearers (22.5 ± 2.3 years) and twenty-four soft CL wearers (23.8 ± 2.2 years) participated in this study. The Keratograph 5M was used to assess the ocular surface. CL users were surveyed on years of CL wear and hours per week. MG visibility was assessed using a previously developed method bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(159 reference statements)
1
3
0
Order By: Relevance
“…The mean MG loss in the upper eyelids seen here was significantly higher in both FLU and non‐FLU CL wearers compared with that of the non‐CL wearing controls, which is consistent with several previous studies 10,11,22,46 . Alghamdi et al 11 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The mean MG loss in the upper eyelids seen here was significantly higher in both FLU and non‐FLU CL wearers compared with that of the non‐CL wearing controls, which is consistent with several previous studies 10,11,22,46 . Alghamdi et al 11 .…”
Section: Discussionsupporting
confidence: 93%
“…The mean MG loss in the upper eyelids seen here was significantly higher in both FLU and non-FLU CL wearers compared with that of the non-CL wearing controls, which is consistent with several previous studies. 10,11,22,46 Alghamdi et al 11 observed the characteristics of the MGs, eyelids and tear film following short (2 ± 1 years), moderate (5 ± 1 years) and long (10 ± 2 years) durations of soft CL wear. They concluded that MG loss in both eyelids was significantly higher in CL wearers of all duration profiles than in non-CL wearers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their use has grown substantially over the years due to their convenience and advancements in materials and design [3][4][5]. Ensuring the safety and effectiveness of these lenses is crucial, not only to provide optimal vision but also to prevent potential eye-related complications [6,7]. One of the critical aspects for ensuring the quality of contact lenses is the detection and elimination of defects, particularly in areas that have a direct interface with the eye [8][9][10].…”
Section: Introductionmentioning
confidence: 99%